Internalisasi Nilai Kedisplinan Melalui Figur Guru PAUD Laki-Laki - Maharani; Syafe’i, Muhammad; Sholihah, Mar’atus; Nurshanti, Yuliana (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This research aims to describe the role of male teachers in instilling discipline in early childhood. The focus of the research is the strategy of instilling discipline in early childhood carried out by male teachers. This research uses a qualitative approach with research subjects being male teachers at RA Ar Rohmah, Cawas District, Klaten Regency. This research uses data collection techniques in the form of observation, interviews and documentation. Data analysis uses Miles and Huberman's interactive model analysis techniques (data reduction, data display, and drawing conclusions). Test the validity of the data using triangulation of data sources and techniques. The research results show that male teachers can accustom children to discipline in worship and related self-control abilities, such as: queuing, taking turns playing, etc. The obstacles experienced were the discontinuity of getting used to it at home and at school and the teacher's lack of attention because he was too busy with his workload. So, it is hoped that schools can invite parents to instill discipline in their children from an early age.